COMPARATIVE HYGIENIC ASSESSMENT OF THE BEHAVIOR AND RESISTANCE OF PESTICIDES IN THE SOILS OF SOUTH-EAST EUROPE WHEN USING FORMULATIONS WITH 3RIVE 3D TREATMENT TECHNOLOGY - Borysenko, Andrii; Аntonenkо Anna; Kondratiuk, Mykola; Omelchuk, Sergii; Melnichuk, Fedir (Polish Journal of Natural Sciences, 2024)
Undoubtedly, one of the important factors that allows to reduce the pesticide load on target and non-target objects is the method of chemical plant protection products (CPPPs) application. The 3RIVE 3D pesticide application system is an innovative technology for plant treatment that allows you to reduce the rate of pesticides used and increase their effectiveness. After the application of Brigade 3Rive 3D, SC formulation using the innovative 3Rive3D technology (soil application with simultaneous sowing of corn seeds) found that on the day of treatment, the level of bifenthrin in the soil was <0.05 mg/kg. On the 3rd day after treatment, the amount of bifenthrin in the soil slightly increased and amounted to 0.083±0.015 mg/kg, on the 7th day the concentration of bifenthrin was 0.06±0.01, which, in turn, is less than the level of the recommended maximum allowable level (0.1 mg/kg). It was established that when applying the Brigade 3Rive 3D, SC formulation using 3Rive3D technology, the half-life of bifenthrin was 3.6 days, which is lower than the average values obtained in other countries of the European region.